Regenerative Medicine And Stem Cell Applications In Wound Healing And Scar Reduction - Ali Shah, Syed Waqas; Mehsam, Syed Ali; Shahid, Aqleema; Ririe, Avrina Kartika; Bangash, Sudhair Abbas (Journal of Neonatal Surgery, 2025)
Background:Stem cell therapies have emerged as promising treatments for wound healing and scar reduction due to their regenerative potential. This study aims to evaluate the perceived effectiveness, safety concerns, and overall impact of stem cell therapies in wound healing and scar reduction. Objective:The primary objective of this study is to assess the perceptions of individuals who have undergone stem cell treatments or are involved in the healthcare sector regarding the effectiveness, safety, and outcomes of these therapies in the context of wound healing and scar reduction. Methods:A quantitative, cross-sectional survey was administered to 250 participants, including patients who have received stem cell therapy for chronic wounds, burns, and scars, as well as healthcare professionals familiar with stem cell applications. The survey included Likert-scale and multiple-choice questions to assess participants' familiarity with stem cell therapies, their experiences with treatment, and their perceptions of its effectiveness and safety. Statistical analysis involved normality testing using the Shapiro-Wilk test, reliability analysis using Cronbach's Alpha, and descriptive and inferential statistics. Results:Shapiro-Wilk normality tests revealed that the variable's Likelihood to Consider Therapy and Concern about Safety significantly deviated from normality (p-value < 0.05). The Cronbach’s Alpha for the reliability of the survey items was 0.652, indicating acceptable internal consistency but suggesting room for improvement in the reliability of the measurement tool. Visual analyses, such as bar and pie charts, were used to present the results of normality tests and reliability outcomes. Conclusion:The findings suggest that stem cell therapies are perceived as effective in promoting wound healing and reducing scarring, though safety concerns, such as immune rejection and tumor formation, persist. The study highlights the need for non-parametric statistical methods and refined survey instruments to improve the reliability and accuracy of the findings. Future research should focus on larger, longitudinal studies to further evaluate the long-term efficacy and safety of stem cell therapies in clinical settings.